Analisis Kemampuan Pemecahan Masalah Ditinjau dari Gaya Kognitif Field Independent Siswa MTs Nahdalatus Shaufiah pada Model Pembelajaran Discovery Learing - Marwazi, Muhammad (Lembaga Yasin AlSys, 2023)
This study aims (1) to examine students' achievement of classical learning mastery in solving mathematical problems with the discovery learning model (2) to analyze the profile of students' mathematical problem solving abilities with field independent cognitive style. The method used in this study is a mix method of concurrent embedded design. This research was conducted at Madrasah Tsanawiyah Nahdlatus Shaufiah East Lombok with samples with field independent cognitive styles which were determined by purposive sampling after they took the GEFT test. Based on the analysis, it was found that (1) Learning with the Discovery learning model achieved classical mastery with KKM 65. (2) In solving problems with polya steps, independent field subjects were able to understand problems, plan solutions, carry out planning and re-examine questions properly so that subjects field independent was able to achieve maximum scores on all problem solving ability test questions.